Assessment of households' responses to the tsunami threat: A comparative study of Japan and New Zealand. (October 2017) - Wei, Hung-Lung; Wu, Hao-Che; Lindell, Michael K.; Prater, Carla S.; Shiroshita, Hideyuki; Johnston, David M.; Becker, Julia S.
Abstract: This study examines households' immediate responses to the potential for tsunami generated by 2011 earthquakes in New Zealand and Japan. Surveys conducted in Christchurch, New Zealand and Hitachi, Japan investigated pre-impact tsunami hazard communication, immediate post-impact expectations that these earthquakes would cause tsunamis, the information sources that respondents used after the shaking stopped, and household evacuation in anticipation of a tsunami. The results reveal some similar patterns as well as some significant differences in the ways that households in the two cities reacted to the tsunami threat. The results show that both cities had very low levels of pre-impact tsunami hazard communication and, possibly as a result, about half of the respondents significantly underestimated tsunami arrival times. Moreover, face-to-face conversation and telephone were the most important sources of disaster information in both communities after the shaking stopped. However, Hitachi households had a higher level of tsunami risk perception, expected sooner tsunami arrival times, and were more likely to evacuate than Christchurch households. Regression analyses indicate that risk perception was the only significant predictor of evacuation and Hitachi location, which was probably a proxy for shaking duration, was the only significant predictor of risk perception. However, these regression equations accounted for little variance, so further research is needed to better understand the tsunami evacuation process.